Benefit valuation predicts gratitude - Forster, Daniel E.; Pedersen, Eric J.; Smith, Adam; McCullough, Michael E.; Lieberman, Debra (Evolution and human behavior, 2017)
Gratitude is an emotion that promotes cooperative relationships and is elicited when an act reveals that an actor values the recipient, especially when the benefit conferred is greater than the recipient expected. But, recipient expectations might vary depending on how much the benefactor is perceived to value the recipient — all else equal, the greater the benefactor is perceived to value the recipient's welfare, the greater the recipient's expectations of benefit delivery. Thus, at a given benefit level, it might be easier to exceed the threshold of expectation in a relationship for which the recipient holds low expectations (e.g., a stranger) as compared to a relationship for which the recipient holds high expectations (e.g., a sibling). This leads to the prediction that cognitive representations of welfare valuation inversely correlate with gratitude: The greater the expected welfare valuation, the more difficult it is to exceed expectations of benefit delivery and, therefore, the less felt gratitude. To test this prediction, we conducted two experiments in which subjects estimated how much they perceived a particular person in their social network to value the subject's welfare. Next, subjects estimated how grateful they would feel if this person provided them with differing levels of benefits. Contrary to our model, we found that gratitude was predicted by the magnitude of the benefit, but not by the recipient's perception of the benefactor's valuation of the recipient.